2021
DOI: 10.3390/coatings11070785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shellac Waterborne Coating Microcapsules on the Optical, Mechanical and Self-Healing Properties of Waterborne Primer on Tilia europaea L. Wood

Abstract: Microcapsules of melamine formaldehyde-coated shellac and waterborne coating were prepared by in situ polymerization at 400, 600, 800 and 1000 rpm. The microcapsules prepared at four different stirring rates were added into the waterborne primer at a concentration of 5.0%, 10.0%, 15.0%, 20.0% and 25.0%. The effects of microcapsules prepared at different stirring rates and the concentration of microcapsules added into the paint film on the optical, mechanical and liquid resistance properties of the paint film w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The specific ingredients are shown in Table 3 . According to previous research [ 24 ], when microcapsules prepared at 600 rpm were added to the coating with the concentration of 5.0%, the comprehensive performance of the coating was the best. Taking sample 1# as an example, the 0.2 g prepared microcapsules were added to 1.8 g primer, the primer was coated to the basswood surface with a brush and then pushed flat with a paint-film preparer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific ingredients are shown in Table 3 . According to previous research [ 24 ], when microcapsules prepared at 600 rpm were added to the coating with the concentration of 5.0%, the comprehensive performance of the coating was the best. Taking sample 1# as an example, the 0.2 g prepared microcapsules were added to 1.8 g primer, the primer was coated to the basswood surface with a brush and then pushed flat with a paint-film preparer.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research focused on the preparation process of microcapsules [ 24 ]. Based on these previous research results, our research considered the coating process of the waterborne coating, and studied the effects of different coating processes on the self-healing performance, mechanical properties, and aging resistance of the coating with microcapsules.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the Fourier-transform infrared (FTIR) analysis, they reported that the number of hydroxyl groups contributing to the 3400 cm -1 absorbance band decreased, which increased the dimensional stability. Yan et al (2021) examined the properties of shellac used in the microencapsulation process. They evaluated the effects of the solutions on linden wood and reported that the elongation at break and gloss values were the highest for the solutions prepared at 600 rpm using 5% shellac.…”
Section: Introductionmentioning
confidence: 99%
“…The paint process in the finishing of European and American furniture not only provides a firm protective layer on the surface of the furniture, but also an important form of load-bearing for the beautiful surface [1][2][3]. In the antique distressing process, the use of paint is a way of expressing the distressed effect of the coating [4][5][6]. It cooperates with the color layer and works together to finally make the surface of European and American furniture show the antique distressed effect [7,8].…”
Section: Introductionmentioning
confidence: 99%